Negative pressure wound therapy (NPWT) as management of surgical site infection (SSI) in spinal fusion surgery - Mislan, Mislan; Waluyo, Agung; Arista, Liya (Media Keperawatan Indonesia, 2024)
Surgical Site Infection (SSI) following spinal fusion surgery may lead to patient morbidity, increased treatment costs, and possible recurrent medical interventions. Negative Pressure Wound Therapy (NPWT) has demonstrated promise in the management of SSI as well as assisting in surgical wound healing. This literature review aimed to evaluate the effectiveness of NPWT as a prophylactic, and treatment of SSI in spinal fusion surgery. The literature review method is conducted by searching research articles comparing NPWT and Standard Wound Dressing (SWD) effectiveness with the relevant cohort or Randomized Controlled Trial (RCT) research design using Embase, Scopus, PubMed, and ScienceDirect databases. The application treads of NPWT for surgical wounds in spinal fusion surgery were also described. The research articles were limited from 2017 to 2022. Six articles fit in criteria of inclusion, three articles were prophylactic management research, and the others were the management of treatment research. Analysis of the articles indicated that NPWT as prophylactic could effectively reduce the incidence of postoperative surgical site infections. NPWT as treatment had less time duration, lower risk of sponge fragment retainment, and fewer procedures to achieve wound closure in spinal fusion surgery. There is currently a lack of strong clinical evidence of its efficacy, so rigorous randomized prospective clinical trials are needed.